Therapeutic Outcomes of Pediatric Acute Myeloblastic Leukemia Patients at a Tertiary Hospital in Bandung, Indonesia - Filbert Lois Marcus; Nur Suryawan; Delita Prihatni (Althea Medical Journal, 2022)
Background: Acute myeloblastic leukemia (AML) is a subtype of leukemia characterized by myeloid infiltration into the bone marrow, blood, and other tissues. AML ranks 5th malignancy in children and the prognosis is poor. After chemotherapy, the outcomes vary. Therefore, this study aimed to provide further insight into the therapeutic outcomes of pediatric AML patients. Methods: This study was conducted with a cross-sectional descriptive method. The data were obtained from the medical records of children diagnosed with AML at the Department of Child Health of Dr. Hasan Sadikin General Hospital in 2017–2019 with the total sampling method. Data including age at determination, gender, laboratory values including hemoglobin, leukocyte, thrombocyte as well as blast cell count on peripheral blood smear were collected. Also, the bone marrow punctures gathered were clustered based on the French-American-British (FAB) classification. Data were presented in tables.Results: In total, 46 data of AML patients were retrieved, with the age category at first diagnosis was >5–12 years (48%) and predominantly males (63%), children with moderate anemia (41%), leukocytosis (35%), severe thrombocytopenia (46%), and blast cell count ≥20% (83%). AML-M2 was the most common subtype (30.4%). The majority of patients (91%) underwent chemotherapy and most (45%) patients died during chemotherapyConclusion: The outcome of AML therapy among children is mostly poor, and particularly die during chemotherapy. Early detection and follow-up of patients to continue therapy are important aspects to reduce the mortality rate of AML.